Impact of Employer Branding and Social Media Informativeness on Job Pursuit Intention Among Generation Z Job Seekers: The Mediating Role of Organizational Attractiveness - Muhammad Fadli; Mia Ayu Gusti (SAFE-Network, 2026)
This study aims to analyze the effect of employer branding and social media informativeness on job pursuit intention among Generation Z and to examine the mediating role of organizational attractiveness. This research uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares. The sample consisted of 160 Generation Z individuals as potential job seekers, with PT. Biro Klasifikasi Indonesia Batam Branch as the research context. The results show that employer branding has a positive and significant effect on job pursuit intention, while social media informativeness has a positive but not significant effect. Both variables significantly influence organizational attractiveness. Furthermore, organizational attractiveness significantly affects job pursuit intention and mediates the relationship between employer branding and job pursuit intention, but does not mediate the relationship between social media informativeness and job pursuit intention.